Pengaruh Laju Pengadukan Terhadap Stabilitas Digester Anaerobik Satu Tahap pada Pembentukan Biogas dari Limbah Cair Pabrik Kelapa Sawit Menggunakan Lab Scale Reaktor Batch - Irvan; Trisakti, Bambang; Azka, Nawalul (Talenta Publisher (Universitas Sumatera Utara), 2020)
Mixing is essential to increase the efficiency of interactions between active microbes and organic matter during the anaerobic digestion process. The purpose of this research is to study the effect of mixing rate on the stability of one stage anaerobic digesters in biogas production in terms of pH and alkalinity. The production of biogas from palm oil mill effluent was carried out in a 6000 ml batch reactor at varying mixing rates: 100 rpm, 150 rpm, 200 rpm, 250 rpm, and 300 rpm. The reactor is operated with a mixture condition maintained at a pH of 7 Â± 0.2 and an operating temperature of 55 Â° C. NaHCO3 is added to the mixture to control and maintain the pH of the mixture. Analysis of pH and alkalinity is carried out every day to see the reactor stability. The best results were obtained at a mixing rate of 200 rpm with the pH produced stable during the process is 7. The alkalinity profile produced at each mixing rate was relatively stable with an alkalinity range is 3500-4500 mg/L. The best mixing rate is 200 rpm with a stable pH and alkalinity and the highest biogas production is 457 ml/day.